A Critique of Trade Disputes Settlement Mechanism in Nigeria: 1968 to 2004 - Anyim, Francis Chukwudike (University of Lagos, 2009)
Full texts attached
https://ir.unilag.edu.ng/handle/123456789/4419
Keywords: Conflict Manifestation; Labour market research; Marxist Perspective; Process of Collective Bargaining; Strike and its effect

The relevance of prior use in trade mark conflicts - Alberts, Riaan Willem (University of South Africa, 2009)
This thesis investigates the role of prior use in common and statutory trade mark law. In the United States a pertinent requirement is priority of use. In the United Kingdom and South Africa, a reputation must be present. In the United Kingdom a plaintiff is required to have goodwill in the country, but in the United States and South Africa it is not required. The conception of a mark does not qualify for protection. It is not required that a business must have actually entered the market. In the United States the general approach is that a plaintiff will not receive protection in a remote area, but regard must be had to zones of natural expansion. British and South African law is the same, and protection may be obtained in areas where there is no trading. Where a dual reputation exists, neither party will be able to act against the other. The mere fact that the user of a mark was aware of the use thereof by another person, does not exclude protection. A trade mark application can be opposed on the basis of another application, combined with use of a mark, or on the ground of prior use. In some instances the fact that a mark has been filed will influence the burden of proof. In general, a registration can be expunged on the same grounds as would constitute grounds of opposition. The concurrent use of a mark can form the basis for the registration of a mark. In the United States, the use must have taken place prior to the filing date of the other party, but in the United Kingdom and South Africa, prior to the own filing date. In the latter two countries, knowledge of a mark is not necessarily exclusionary. Prior use is generally accepted as a defence to an infringement action. It is, however, noted that in various countries, it is only use prior to the relevant date that will be protected, and there is not necessarily a right to extend the scope of use concerned.
Keywords: Common law trade marks; Competencia; Competition law; Intellectual property; Trade marks; Unfair competition; Unlawful competition

Selective legal aspects of bank demand guarantees - Kelly-Louw, Michelle (University of South Africa, 2009)
Bank demand guarantees have become an established part of international trade. Demand guarantees, standby letters of credit and commercial letters of credit are all treated as autonomous contracts whose operation will not be interfered with by courts on grounds immaterial to the guarantee or credit itself. The idea in the documentary credit transaction/demand guarantee transaction is that if the documents (where applicable) presented are in line with the terms of the credit/guarantee the bank has to pay, and if the documents do not correspond to the requirements, the bank must not pay. However, over the years a limited number of exceptions to the autonomy principle of demand guarantees and letters of credit have come to be acknowledged and accepted in practice. In certain circumstances, the autonomy of demand guarantees and letters of credit may be ignored by the bank and regard may be had to the terms and conditions of the underlying contract. The main exceptions concern fraud and illegality in the underlying contract. In this thesis a great deal of consideration has been given to fraud and illegality as possible grounds on which payment under demand guarantees and letters of credit have been attacked (and sometimes even prevented) in the English, American and South African courts. It will be shown that the prospect of success depends on the law applicable to the demand guarantee and letter of credit, and the approach a court in a specific jurisdiction takes. At present, South Africa has limited literature on demand guarantees, and the case law regarding the grounds upon which payment under a demand guarantee might be prevented is scarce and often non-existent. In South Africa one finds guidance by looking at similar South African case law dealing with commercial and standby letters of credit and applying these similar principles to demand guarantees. The courts, furthermore, find guidance by looking at how other jurisdictions, in particular the English courts, deal with these issues. Therefore, how the South African courts currently deal/should be dealing/probably will be dealing with the unfair and fraudulent calling of demand guarantees/letters of credit is discussed in this thesis.
Keywords: Bank guarantee; Demand guarantee; Documentary credit; Fraud; Freezing injunction; Garantie bancaire; Letters of credit; Suretyship and guaranty

A critical analysis of problem areas in respect of assets of insolvent estates of individuals - Evans, Roger Graham (University of Pretoria, 2009)
The Law of Insolvency in South Africa is regulated by the provisions of the Insolvency Act 24 of 1936, with foundations in our common law, which has been influenced by different legal systems from Western Europe. But currently there is also other legislation affecting the insolvent debtor and the property in the insolvent estate. The courts too have had to formulate rules to govern aspects of insolvency law in South Africa. These variables created problem areas in insolvency law and in respect of the of the policies upon which the insolvency system hinges. The predominant policy in South African insolvency is the collection of the maximum assets of the debtor for the advantage of creditors in insolvent estates. This strict creditor orientated approach created further problem areas in respect of assets in the insolvent estates of individual debtors. If advantage to creditors cannot be shown in an application for the sequestration of a debtor’s estate, a court will refuse to grant that order. This strict policy overshadows policy concerns in respect of assets in insolvent estates, and regarding exemption law in respect of those assets. This has resulted in insolvency law reformers in South Africa missing the bigger picture, namely, that South Africa is a creditor driven developing society. It is conceivable that in the transformed South Africa, and in the present world economic chaos, there will be an escalation of sequestrations of the estates of individual debtors. Bearing this in mind, a reformed insolvency law system must become more debtor friendly. A change in the philosophy is needed in favour of an exemption policy for insolvent estates. Exemption policy must be based on the interest of the debtor and his dependants, his dignity, creditor and third party interests, social welfare, and human rights imperatives within the South African constitutional framework. Exemption policy must be linked to the policy of a “fresh start” for the debtor. The different policies in insolvency however create a conflict of interest among the different stakeholders, particularly regarding the assets in insolvent estates, thereby creating problem areas. In this thesis several problem areas are identified and critically analysed. The position of property included in, and excluded from, individuals’ insolvent estates is investigated from a brief historical perspective, and in a brief comparative survey of the insolvency systems of the United Kingdom and the United States of America. Acute problem areas are critically analysed in detail, and the constitutional impact on property in insolvent estates is considered in a separate chapter. The South African Law Reform Commission’s review of South African insolvency law is critically analysed in a chapter of this thesis, concluding that the Commission’s review is inadequate. This thesis concludes that there is a need to reform the insolvency system in South Africa and proposes a way forward in respect of property included in, and property excluded or exempt from insolvent estates. This thesis states the law to the end of October 2008.
Keywords: Advantage to creditors; Creditor; Debtor; Disposition of property

Labour law implications of the transfer of an undertaking - Smit, Nicola (University of Johannesburg, 2009)
This thesis provides a comprehensive analysis of the legal, social, and economic consequences of business transfers on employment contracts, focusing on South African law and its comparison with international standards. It critically evaluates the automatic transfer of employment contracts, the protection of employee rights, and the legal complexities surrounding insolvent undertakings.
Keywords: Labour law; Labour legislation; Transfer (Law)

Rethinking the world trade order: towards a better legal understanding of the role of regionalism in the multilateral trade regime - Abualethem Nsour, Mohammad Fahed (McGill University, 2009)
Regional Trade Agreements (RTAs) have proliferated at an unprecedented pace since the creation of the World Trade Organization (WTO). Although the WTO legally recognizes countries’ entitlement to form RTAs, neither the WTO nor parties to RTAs have an unequivocal understanding of the relationship between the WTO and RTAs. In other words, the legal controversies, the result of uncertainty regarding the application of the WTO/GATT laws, risk undermining the objectives of the multilateral trade system. This thesis tackles a phenomenon that is widely believed to be heavily economic and political. The thesis highlights the economic and political aspects of regionalism, but largely concentrates on the legal dimension of regionalism. The main argument of the thesis is that the first step to achieving harmony between multilateralism and regionalism is the identification of the legal uncertainties that regionalism produces when countries form RTAs without taking into account the substantive and procedural aspect of the applicable WTO/ GATT laws. The thesis calls for the creation of a legal instrument (i.e. agreement on RTAs) that combines all of the applicable law on RTAs, and simultaneously clarifies the legal language used therein. Likewise, the WTO should have a proactive role, not merely as a coordinator of RTAs, but as a watchdog for the multilateral system that has the power to prosecute violating RTAs. The author is aware that political concerns are top priorities for governments and policy makers when dealing with the regionalism problematic. Hence, legal solutions or proposals are not sufficient to create a better international trade system without the good will of the WTO Members who are, in fact, the players who are striving to craft more regional trade arrangements.
Identifier: https://escholarship.mcgill.ca/concern/theses/3r074w80k
Keywords: GATT; International Trade; Regional Trade Agreements (RTAs); WTO

Harmonisation of procedural law in international commercial arbitration - Chang, Mann-Long (University of Stirling, 2009)
The principle of party autonomy is widely accepted in the practice of international commercial arbitration. However, it still encounters certain limitations in its applications, especially for the fact that the demands of natural justice and the public good cannot be neglected by the parties. The various states in the international system have and operate peculiar systems of mandatory rules and public policies, which tend to impart significantly on the arbitral procedure, thereby creating a situation of discordance of outcomes of arbitration in different countries. For this reason, this writer intends to examine ways by which the various procedural laws can actually be harmonised. This thesis shall therefore focus on the discordances and confusion that often arise in the interacion of the various laws that may be applicable to the arbitral process in International commercial arbitration, as well as ways of achieving a harmonisation of these laws.
Keywords: Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; International commercial arbitration

Libyan Attitudes towards Islamic Methods of Finance: An Empirical Analysis of Retail Consumers, Business Firms and Banks - Gait, Alsadek Hesain Abdelsalam (Griffith University, 2009)
Libya is a predominately Muslim country where Islamic finance has not yet been established. However, given the current extensive program of financial reform in Libya and the rapid growth and appeal of Islamic finance in comparable economies, there is growing pressure for a system of Islamic finance to be provided. There is then a pressing need for research into the prospects for Islamic finance from a consumer and provider perceptive to inform this debate and thereby meet the needs of policymakers, financial service providers and prospective users. Accordingly, this study of Libyan attitudes towards Islamic methods of finance, the first study attempted in the Libyan context and one of few studies globally, applies a model derived from the Theory of Reasoned Action to analyse attitudes towards Islamic finance. The particular focus is to understand how the Theory of Reasoned Action can be used for predicting and understanding attitudes towards the potential use of Islamic methods of finance by Libyan retail consumers, business firms and banks. Four main research questions are posed to address this objective. First, does awareness of Islamic methods of finance influence attitudes towards the use of Islamic finance? Second, do socioeconomic, demographic and other factors influence attitudes towards Islamic finance? Third, what are the principal motivating factors towards the potential use of Islamic finance? Finally, is religion the major influence on the likelihood of engaging in Islamic finance? Three surveys of 385 retail consumers, 296 business firms and 134 bank managers in Libya are conducted in 2007/08 to achieve this objective. Descriptive analysis and multivariate statistical analysis (including factor analysis, discriminant analysis and binary logistic regressions) are used to analyse the data. The principal findings are that awareness of Islamic methods of finance and socioeconomic, demographic and business characteristics are key determinants of the likelihood of the use of Islamic finance. Further, religion plays a key, though not the only, role in influencing these attitudes. The thesis findings are of key importance in informing future financial industry practice and financial policy formation in Libya.
Accepted: 2018-01-23T02:48:08Z
Keywords: Finance; Financial policy; Financial reform; Islam; Islamic finance; Libya

Income splitting, settlements and avoidance: taxing the family on business profits - Loutzenhiser, Glen (Oxford University, 2009)
In a progressive income tax system with an individual tax unit, high-rate taxpayers have an incentive to split income with lower-rate family members to minimise the family’s total tax burden. This raises equity and neutrality concerns. Adopting a spousal tax unit limits the gains from income splitting, but the individual is the better choice on privacy, autonomy, equality, definitional, marriage neutrality and work incentive grounds. Once the individual is chosen as the income tax unit, the control model provides a strong policy basis for attributing both earned and unearned income to individuals. Income splitting, however, undermines this model as well as the individual tax unit. This thesis focuses on the UK’s approach to income-splitting in family businesses. The relevant UK income tax rules, particularly the settlements provisions, are inadequate for the task. Various possible reforms are examined. Incorporating a transfer pricing or ‘reasonableness’ test into the settlements provisions would strengthen these rules, but would make taxpayer compliance with an uncertain regime even more difficult. Another option is to expand the scope of employment tax by moving the borderline between employees and the self-employed or companies. Deeper structural reforms could be made to enhance the neutrality of taxation on different legal forms of economic activity. This would reduce the incentives to incorporate for tax savings, including from income splitting. Integration of income tax and NICs is one such option; a dual income tax is another. A TAAR or GAAR also could be pursued. Ultimately, some combination of these various reform options could provide a partial solution to this challenging issue.
Keywords: Family taxation; Husband and wife; Income splitting; Settlements; Taxation

A balancing act: a framework for participation of non-state actors in the World Trade Organization - Majlessi, Mohammad (McGill University, 2009)
This thesis focuses on the interaction of two categories of non-state actors, private sector corporate actors and non-governmental organizations, with states in the context of the World Trade Organization (WTO) through a lens of public international law. It builds on the premise that the notion of states as the only subjects of international law is not adequate for a modern system of global governance, as it does not reflect the realities of fast-paced globalization and increased co-operation in a world where the boundaries of the private and public are increasingly blurred. It does not necessarily provide solutions for participation of non-state actors in the WTO, but demonstrates that developments in international relations warrant more space for participation of non-state actors, and that the current system of the WTO fails to provide sufficient space for participation. The thesis argues that, for both historical and pragmatic reasons, developments in the areas of GATT and international trade law occurred outside their natural course, leading to the myth of a “self-contained” trade regime not part of public international law. The WTO, unlike its predecessor, enjoys a proper institutional framework and mandate; one can no longer use the excuse of institutional handicap for excluding it from the system of global governance. Liberalization of international trade has far-reaching consequences which are not limited to the trade arena and the WTO, its member states, and scholars of international trade law have to assume their role in the broader context of an international legal order. Non-state actors’ formal participation can contribute to striking a balance between different forces and interests at work in the area of trade liberalization and its interplay with other non-trade issues. After setting the framework for the study, the thesis outlines modes of participation of non-state actors in the creation and modification of WTO law as well as in its enfor
https://escholarship.mcgill.ca/concern/theses/nv9354568
Keywords: Balancing act; International Trade; WTO; World Trade Organization

Status Ambiguity and Conflict in the Market - Tan, David (Emory University, 2009)
My main theoretical contention is that status hierarchies provide a source of guidance to firms for resolving disputes. A status hierarchy implies a system of deference rules among firms. When disputes arise, deference rules can provide a basis for shared expectations and protocols of conduct about how technical ambiguities should be resolved. In many contexts, technical merit is difficult to assess. However, deference rules can operate as social conventions to which firms default, helping to align potentially incompatible expectations. Within this general framework, my dissertation examines how competitors in the semiconductor industry manage uncertain and frequently overlapping patent rights. In practice, patent rights are highly imperfect legal instruments when it comes to demarcating each firm's contributions to innovation in the industry. Patent disputes arise because of the ambiguity this creates about how much of the collective market returns to innovation each firm is entitled to receive. Despite the prolific patenting and propensity for disputes, the industry has remarkably not ground to a halt from runaway litigation. Litigation events, while significant, are rare. I suggest that this degree of order is, at least partly, attributable to status processes. Status can operate as a stabilizing force in the market, helping to generate orderly competition in the face of disputes. To examine whether this is the case in the semiconductor industry, I theorize that disputes are less easily resolved when the parties involved face greater status ambiguity, i.e. are less clearly differentiated from one another in status. Under status ambiguity, deference rules lose the rule-like, universal quality that makes them persuasive in resolving disputes. This has two consequences. First, firms facing low status ambiguity are less likely to be involved in patent litigation than are firms facing high status ambiguity. Patent litigation events represent failures to resolve patent disputes out of court. Second, firms facing low status ambiguity increase their product line sizes more than do firms facing high status ambiguity. The threat of difficult-to-resolve patent disputes represents a cost that can deter firms from bringing products to market.
Permanent URL: https://etd.library.emory.edu/concern/etds/9g54xj191?locale=en
Keywords: Litigation; Patent; Semiconductor; Status